Cost-effectiveness analysis of internet-mediated cognitive behavioural therapy for depression in the primary care setting: results based on a controlled trial. Issue 6 (14th June 2018) - Holst, Anna; Björkelund, Cecilia; Metsini, Alexandra; Madsen, Jens-Henrik; Hange, Dominique; Petersson, Eva-Lisa L; Eriksson, Maria CM; Kivi, Marie; Andersson, Per-Åke Å; Svensson, Mikael
Abstract : Objective: To perform a cost-effectiveness analysis of a randomised controlled trial of internet-mediated cognitive behavioural therapy (ICBT) compared with treatment as usual (TaU) for patients with mild to moderate depression in the Swedish primary care setting. In particular, the objective was to assess from a healthcare and societal perspective the incremental cost-effectiveness ratio (ICER) of ICBT versus TaU at 12 months follow-up. Design: A cost-effectiveness analysis alongside a pragmatic effectiveness trial. Setting: Sixteen primary care centres (PCCs) in south-west Sweden. Participants: Ninety patients diagnosed with mild to moderate depression at the PCCs. Main outcome measure: ICERs calculated as (CostICBT −CostTaU )/(Health outcomeICBT −Health outcomeTaU )=ΔCost/ΔHealth outcomes, the health outcomes being changes in the Beck Depression Inventory-II (BDI-II) score and quality-adjusted life-years (QALYs). Results: The total cost per patient for ICBT was 4044 Swedish kronor (SEK) (€426) (healthcare perspective) and SEK47 679 (€5028) (societal perspective). The total cost per patient for TaU was SEK4434 (€468) and SEK50 343 (€5308). In both groups, the largest cost was associated with productivity loss. The differences in cost per patient were not statistically significant. The mean reduction in BDI-II score was 13.4 and 13.8 units in the ICBT and TaU groups, respectively. The mean QALYs per patient was 0.74 and 0.79 in the ICBT and TaU groups, respectively. The differences in BDI-II score reduction and mean QALYs were not statistically significant. The uncertainty of the study estimates when assessed by bootstrapping indicated that no firm conclusion could be drawn as to whether ICBT treatment compared with TaU was the most cost-effective use of resources. Conclusions: ICBT was regarded to be as cost-effective as TaU as costs, health outcomes and cost-effectiveness were similar for ICBT and TaU, both from a healthcare and societal perspective. Trial registration number: ID NR 30511.